Development of Learning Modules Based Numbered Head Together (NHT) on Substance Pressure Material at the Junior High School Level - Mustika, Cut Rizki; Aida, Nur; Sihaf, Ainun Nazah (Asian Journal of Science Education, 2023)
Based on observations, the teaching materials used in the learning were only textbooks. This study aims to design and determine the feasibility level, and students' responses to the learning module. This research uses Research and Development (RD) research with the ADDIE model. The subjects of this study included 3 material expert validators, 3 media expert validators, and 6 students of Subulussalam City Integrated Islamic Junior High School. The data analysis techniques used are qualitative and quantitative descriptive analysis techniques that describe the results of the validity and practicality test of NHT-based modules. The instruments used in this study were material expert validation sheets, media experts, and questionnaire sheets. The research results obtained from material expert validation were 94.4% and media expert validation was 95.5%, so that overall the percentage of results feasibility was 94.95% with very feasible criteria. The student response results obtained were 95.5% with very interesting criteria. As a result, it is possible to conclude that the learning module can be used in the learning process.